Study of the degree of gall bladder wall thickness and its impact on outcomes following laparoscopic cholecystectomy in JSS Hospital - B. J., Sharath Chandra; Bose, Rahul (International Surgery Journal, 2018)
Background: Elective laparoscopic cholecystectomy (LC) is presently the gold standard for management of symptomatic gall stone disease, replacing open cholecystectomy. The objective of this study was to measure gall bladder wall thickness preoperatively on ultrasound in patients with symptomatic gallstone disease and to establish its role as a prognostic indicator for complications during or following laparoscopic cholecystectomy. Methods: Gall bladder wall thickness was measured by ultrasonography in 151 patients who presented with Gallstone disease and underwent laparoscopic cholecystectomy for gallstone disease in the JSS Hospital in the given time period. They were then divided into 4 groups depending upon the wall thickness. Normal (upto 2 mm), mildly thickened (>2 to 4 mm), moderately thickened (>4 to 6mm), severely thickened (>6 mm). The incidence of intra and post-operative complications were monitored and compared between the four groups. Results: The incidence of complications was found to be significantly higher in patients with mildly and moderately thickened gall bladder walls (53.1% and 83.3% respectively) as compared to gall bladders with normal wall thickness (10.5%). Average postoperative length of stay in hospital was significantly higher in patients with thickened walls as compared to patients with normal thickness. Conclusions: With wall thickness of greater than 2 mm, the complication and conversion rates are extremely high. An increase in the thickness of the gall bladder wall leads to an increased risk of complications and conversions as well as an increased length of stay in hospital post operatively. Patients with thickened gall bladder walls accounted for only 30% of the study population but they experienced the maximum number of complications (72.5%) and conversions to open (71.4%).